Analysis of the mechanical properties of the single layered braid reinforced thermoplastic pipe (BRTP) for oil & gas industries - Malik Abdul Karim; Mohamad Zaki Abdullah; Ahsan Waqar; Ahmed Farouk Deifalla; Adham E. Ragab; Muhammad Khan (Results in Engineering, 2023)
Reinforced thermoplastic pipes (RTPs) are instantly being broadly scrutinized as a feasible surrogate for metallic pipes due to their superior corrosion resistance, low weight, and low maintenance worth, they have three primary layers inner, outer, and reinforcement. Process parameters for manufacturing reinforced layers are critically essential to enhancing the mechanical performance of RTPs. However, limited comparative research on the impact of braiding parameters on RTP’s mechanical characteristics appears to be publicly available. Therefore, this study examines how these variables affect the mechanical characteristics of braid RTP. This new class of braid RTP is constructed of an HDPE liner pipe, over-wrapped with a single braid layer of resin glass fiber. L9 Taguchi orthogonal array design for experiments was used to create specimens. Furthermore, specimens were subjected to tensile and compression to assess their mechanical properties. Epoxy and ±75 were the most promising parameters in achieving the highest number of tensile and compression properties among choices of thermoplastic polymer matrices and braid angles, respectively. ANOVA suggested that both parameters are significant and significantly impact the mechanical properties of the prototype braid RTP. Also, A1B3 is considered the best combination for producing braid RTP with higher mechanical performance; no notable interaction among factors was found.